Ultraestructura del bambú Guadua amplexifolia (Poaceaea: Bambusoideae) presente en Costa Rica - Montiel, Mayra (2006)
We used a scanning electron microscope to study the ultrastructure of vegetative and floral parts of Guadua amplexifolia from Costa Rica, a bamboo characterized by a solid culm in the base and a small lumen in the distal part. The most evident characteristics were: epidermic cells with operculated-oblique papillae in the palea, the great amount of ceric papillae forming rosettes in the adaxial section of the leaf blade, the abundance of silica cells in the lemma, the numerous trichomes of the palea and lemma, and the abundance of starch in the parenchymatous tissue. Leaves in the particular genotype under study were 7-16 cm long and 3 cm width, while previous studies reported 16-24 cm long and 3-5 cm width for the species. Rev. Biol. Trop. 54(Suppl. 2): 21-28. Epub 2006 Dec. 01.